KUALITAS KEBERANIAN MARTHA TILAAR (PEMIMPIN MARTHA TILAAR) DALAM KONTEKS BISNIS BERBASIS TANAMAN UNTUK KECANTIKAN DAN OBAT - Nuah P. Tarigan; Christian Siregar; Hondi Panjaitan (Universitas Trisakti, 2012)
By conducting research on the quality of the courage of the writers and all who read this research will increasingly aware that quality of courage these elements can be built, so it is not just a personality, but also the behavior of an individual student or professional workers and entrepreneurs even public officials in the territory of the Republic of Indonesia this is characteristic of togetherness or